Percepção do trabalhador da indústria calçadista sobre depressão e cuidado - Rangel, Ana Lívia Pongitori Gifoni (2017)
WORLD HEATH ORGANIZATION considers depression As a global public health problem that remains poorly diagnosed in primary care services and, when it is detected, is treated inappropriately and has serious impacts on the lives of workers and organizations. The presente study has as general objective to know the perception of worker of the footwear industry on his own process of depression and the care to which they were submitted. The specific objectives are: to describe the course of the worker to close the medical diagnostic, to identify towhich referral /treatment the worker was submitted, from themedical diagnostics, to verify the current condition ofthe worker after treatment and to relate recommendations for the improvementof the process to promove the healthof workers in industry. The qualitative exploratory methodology was applied to Sobral-Ce shoe industry workers. Inclusion criteria were: activeemployees who were diagnosed or removed for depression between 2014 and 2015, living in Sobral. The data collection was performed through a semi-structured interview and the data were analyzed through the thematic analysis methodology. Regarding the ethical aspects,the research was approved by UVA Research Ethics Committee with CAAE: 67823817.5.0000.5053 and OPINION: 2.158.033 and participants signed the Informed Consent Term. The analysis points out that referrals to specialized services are not being effective enough to guarantee adherenceto treatment, avoid abandonment, and contribute to worker recovery and better management of the disease. The analysis concludes that depression continuesas a disease difficult to be recognized and faced by workers and, when diagnoseg, is treated primarily through pharmacotherapy. Psychotherapy, which is recommendedin most cases as a complementary treatment to tje medication, has notreached the required adherence so that is can fulfill its role. Treatment is perceived as something of outstanding value but, workers do not realize the existece of a therapeutic Project, the bonds are fragile and there is little involvement with the Family. The results point out aspects relatedto the care servisse and work organization that can improve, among them, the leadership position, the treatment andrelationship between managers and workers, the management of routine of work, the accompaniment to the workersand the access to psychotherapy.